2017
DOI: 10.1177/0018720816672308
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Continuous Operator Workload With a Hybrid Scaffolded Neuroergonomic Modeling Approach

Abstract: Objective: We aimed to predict operator workload from neurological data using statistical learning methods to fit neurological-to-state-assessment models.Background: Adaptive systems require real-time mental workload assessment to perform dynamic task allocations or operator augmentation as workload issues arise. Neuroergonomic measures have great potential for informing adaptive systems, and we combine these measures with models of task demand as well as information about critical events and performance to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…That study concluded that only FD could be used to evaluate human mental workload. Several computational intelligence algorithms have been used to classify and detect mental workload levels, such as SVM [72,138,[190][191][192], ANN [193][194][195], and random forest (RF) [196].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…That study concluded that only FD could be used to evaluate human mental workload. Several computational intelligence algorithms have been used to classify and detect mental workload levels, such as SVM [72,138,[190][191][192], ANN [193][194][195], and random forest (RF) [196].…”
Section: Plos Onementioning
confidence: 99%
“…Furthermore, a queuing network-based computational neuroergonomic architecture [234] is a potential approach to the development of recognition and adaptive systems that can make correct decisions in a short period of time [235]. Although some researchers have predicted current human states using machine learning algorithms, the successful application of such algorithms has been limited [236]. Another shortcoming is the lack of designs with ecological validity.…”
Section: Plos Onementioning
confidence: 99%
“…Physiological measures are frequently used to classify the level of mental effort (Borghetti, Giametta, & Rusnock, 2017;Marinescu et al, 2018). Different physiological measures, such as skin conductance, temperature, heart rate (HR), or pupil dilatation, are frequently used to establish the level of sympathetic nervous system activity (Capa, Audiffren, & Ragot, 2008).…”
Section: Physiological Reactivity Related To Mental Effortmentioning
confidence: 99%
“…Human monitoring enables computer systems to interpret and predict the human cognitive or physical states. For example, random forest classification algorithms have been successfully applied to predict driver drowsiness based on steering angles of the vehicle (McDonald, Lee, Schwarz, & Brown, 2013) and operator workload based on EEG (Borghetti, Giametta, & Rusnock, 2017). Human monitoring is essential to adaptive automation.…”
Section: Game-changing Applicationsmentioning
confidence: 99%